The Washback Effect of Cat on Students’ Learning in EFL Classroom - Ida Dwi Safitri (Hasanuddin University, 2018)
This study explores how the students learn after CAT (computer-assisted test) is applied in teaching and learning English. CAT employs computer applications for evaluating test takers’ performance in learning English. The main concern of this study is to investigate the washback effect of CAT on students’ learning in EFL classroom in Indonesia. Washback itself is defined as the influence of the tests or assessments in teaching and learning. It means that washback effect indicates the critical role of the tests or assessments on students, teachers and societies. In a qualitative design, the findings show that there are washback effects of CAT on students’ learning in EFL classroom.